Test and Disseminate Technologies to Intensity Vegetable Mono-cropping - International Institute of Tropical Agriculture; World Vegetable Center; Savanna Agricultural Research Institute (International Food Policy Research Institute, 2015)
This data study explores integrating vegetable into cereal-legume cropping productions systems in Ghana. Project title: AfricaRISING - Sustainable Intensification of Cereal-based Farming Systems in the Guinea-Sudan-Savanna of Ghana and Mali. Project abstract: Four vegetable crops will be compared across subsets of 30-50 households in each of the 3 northern regions using two planting densities and they are Amaranth for Upper West Region, Jute Mallow for the Northern region and Roselle for the Upper East region. Three fruit vegetables (Okra in all the regions), African eggplant and tomato in the other two regions and one spice vegetable (Pepper), in all the three regions. Project website: http://africa-rising.net